COMMUNITY MOVEMENT IN WASTE MANAGEMENT (Case in Cikapundung River Basin in Bandung City) - Bintarsih Sekarningrum; Desi Yunita (Jurnal Community, 2015)
There is a connection between the behaviour of throwing waste into the river with the community perspective about river. The behaviour of people throwing waste into the river assosiated with the lack of availability of facilities dispose of waste in the area and looked at the river as an object or place that is easiest to throw garbage into the river. Related to these problems, this research describes the community who doing the social movement in waste management a long the river, as well as analyzing patterns of community organizing in waste management.The approach used is a qualitative method of data collection techniques consisted of observation, interviews and focus group discussions. Research shows that the government has made efforts through the program "Clean Cikapundung River", and waste management efforts, sediment transport and manufacture kirmir on a riverbank to prevent abrasion. However Cikapundung still dirty and full of trash. To overcome these problems, there are many communities who awakened and stirred to make an effort in order Cikapundung no longer become dumping grounds. The movement to strive for existence of the river can be used again as an important source of livelihood for the people. Community was formed to instill public awareness of the environment, especially rivers, in the form of an appeal and a call to people not to throw garbage into the river and do the cleaning and arrangement along the river so that the river Cikapundung clean and free of trash based on solidarity and mutual assistance. The social movements showed public awareness to make changes to their environment, especially the problem of waste in the river.